PERAN Peran Balai Besar Guru Penggerak Merangsang Upaya dan Kualitas Guru Penggerak Untuk Kemajuan Pendidikan di Indonesia: BBGP, GURU, KUALITAS - Chusni, Amul; Afifah, Dina; Alfin Syirojuddin, Muhammad; Sulaswari, Misroh (Jurnal Penelitian dan Pendidikan IPS, 2023)
This study aims to show how the role of BBGP in advancing education in Indonesia is to find out the magnitude of the influence of Indonesian education in advancing the efforts and quality of teachers. With that, teachers must be able to adapt to government regulations. The role of the teacher is very important for educational staff, namely as professional education staff, teachers must be able to provide quality learning so that they are educated and a generation that can compete in the era of globalization. So that the teacher must have four competencies, namely pedagogic, social competence, professional competence, personality competence if the teacher is capable of independent thinking and is able to provide stimulus to students able to use their reasoning power intelligently and able to use their thinking power or creativity according to the talents of students' interests. The research method used is a qualitative type of research. This research was built to find out in-depth understanding and discoveries in the field that will be examined. The conclusion is the strategy of the Great Hall of driving teachers in the advancement of education in Indonesia now, starting with quality from human resource sources and analyzing teacher quality in line. according to BBGP mapping and what efforts need to be made by teachers to improve this quality.